Double Closed-Loop PI Control of Three-Phase Inverters by Binary-Coded Extremal Optimization - Dai, Yu-Xing; Wang, Huan; Zeng, Guo-Qiang (IEEE access, 2016)
How to design an effective and efficient double closed-loop proportional-integral (PI) controller for a three-phase inverter to obtain satisfied quality of output voltage waveform is of great practical significance. This paper presents a novel double closed-loop PI controller design method for a three-phase inverter based on a binary-coded extremal optimization (BCEO) algorithm. The basic idea behind the proposed method is first formulating the optimal design problem of double closed-loop PI controller for a three-phase inverter as a typical constrained optimization problem, where the total harmonic distortion and the integral of time weighted absolute error of output voltage waveform are weighted as the optimization objective function, and then a BCEO algorithm is designed to solve this formulated problem. The superiority of the proposed method to Z-N empirical method, binary-coded genetic algorithm, binary-coded particle swarm optimization is demonstrated by both simulation and experimental results on a 20-kW three-phase inverter with nominal and variable loads.